Fig. 6 in Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions ... - Kiel, Steffen; Sami, Marco; Taviani, Marco (Zenodo, 2023)
Fig. 6. Neritimorpha Golikov & Starobogatov, 1975 and Caenogastropoda Cox, 1960 from the Calcari a Lucina seep deposits in northern Italy. A–B. The phenacolepid (Neritimorpha) Thalassonerita megastoma Moroni, 1966, Le Colline (MSF 1223), internal mold showing columellar muscle scars. C–E. The elachisinid (Caenogastropoda) Laeviphitus sp. C. Small specimen with preserved protoconch, from Ca' Rovereti (NRM Mo 204837). D. Close-up on transition between proto- and teleoconch, from Ca' Rovereti (NRM Mo 204838). E. Tall specimen (MSF 1204) from Le Colline. F–G. Naticidae indet. sp. 1. F. Shell embedded in rock matrix, from Castiglion dei Pepoli (MGGC 22304). G. Operculum (MSF 1218). H. Naticidae indet. sp. 2 from Guzzano (MGGC 22305). I–K. Pisanianura? pusilla Bellardi 1872, from Castel di Casio. I. Specimen with remains of siphonal canal and shell sculpture (MGGC 22306). J. Small, internal mold (MGGC 22307). K. Large specimen with preserved shell (MGGC 22308). L. Semicassis aff. reticulata (Bellardi & ... : Published as part of Kiel, Steffen, Sami, Marco & Taviani, Marco, 2023, Mollusks (Gastropoda, Bivalvia) from Miocene cold-seep deposits in northern Italy: revisions and additions, pp. 115-160 in European Journal of Taxonomy 910 on page 131, DOI: 10.5852/ejt.2023.910.2365, http://zenodo.org/record/10350702 ...